Achieving food security and industrial development in Malawi: Are export restrictions the solution? - Aragie, Emerta A.; Pauw, Karl; Pernechele, Valentina (Elsevier, 2018)
This study assesses the economy-wide effects of Malawi’s long-term maize export ban, which was only recently lifted, and a proposed oilseed export levy intended to improve food security and support local processing industries, respectively. We find that maize export bans only benefit the urban non-poor, while poor farmers’ incomes and maize consumption levels decline in the longer run. The oilseed export levy also fails to achieve its long run objectives: even when tax revenues are used to further subsidize food processors, their gains in value-addition are outweighed by declining agricultural value-addition. More generally, these results show that while export restrictions may have the desired outcomes in the short run, production responses may render the policies ineffective in the medium to long run. Ultimately, such restrictive policies reinforce a subsistence approach to agriculture, which is inconsistent with the stated economic transformation goals of many Sub-Saharan countries.